Co-targeting Aurora kinase A and Bcl-2 synergistically inhibits the viability in double-hit lymphoma cells - Kong, Ling-Zhe; Jia, Xiao-Hui; Song, Zheng; Qiu, Li-Hua; Li, Lan-Fang; Qian, Zheng-Zi; Zhou, Shi-Yong; Liu, Xian-Ming; Ren, Xiu-Bao; Meng, Bin; Fu, Kai; Wang, Ping; et al. (Translational Cancer Research; Vol 6, No 4 (August 31, 2017): Translational Cancer Research, 2017)
Background: Double-hit lymphoma (DHL) is a rare high-grade B-cell lymphoma characterized by MYC and Bcl-2 or Bcl-6 gene translocations. The treatment of DHL remains a substantial clinical challenge due to remarkably undesirable outcomes. Innovative drugs or combination treatment strategies need to be developed to improve the prognosis of DHL patients. The purpose of this study was to investigate the combination treatment of a novel Aurora kinase A (Aurka) inhibitor, named alisertib (MLN8237) and a selective Bcl-2 inhibitor, named ABT-199 in vitro, and to explore the underlying mechanisms in human DHL cell lines. Methods: Cell proliferation was assessed using MTS assay in DHL cells treated with alisertib and ABT-199. Synergistic effects between two drugs were analyzed based on combination index (CI) values. Cell cycle and apoptosis were detected through flow cytometry. The expression of drug-targeted proteins, cell-cycle proteins as well as apoptosis-related proteins were detected by Western blot. Results: Alisertib and ABT-199 alone exhibited a relatively modest cytotoxicity in a concentration- and time-dependent manner, but the combination treatment produced stronger antitumor efficacy and synergistically suppressed the DHL cell growth. Otherwise, the combination treatment between alisertib and ABT-199 arrested the cell cycle in the G2/M phase at respectively lower concentrations (2/5 IC50), while the higher concentrations (3/5 IC50) resulted in a striking increase of cell apoptosis. Further studies demonstrated that both alisertib and ABT-199 downregulated the expression of cyclin-dependent kinase 1 (CDK1) and cyclin B1, but upregulated the p21 and p53 expression. The combination treatment enhanced the expression of cell intrinsic apoptotic proteins, including cleaved Poly ADP-ribose polymerase (PARP) and caspase-3. In addition, the combination treatment almost completely inhibited the expression of drug-targeted proteins, including MYC and Aurka phosphorylation. However, alisertib and ABT-199 did not alter the Bcl-2 expression. Conclusions: Alisertib and ABT-199 had synergistic effects on the inhibition of cell viability, induction of cell G2/M phase arrest and apoptosis in DHL cells. The underlying mechanism of synergism was associated with the p53/p21 and cell intrinsic apoptotic pathways. Our findings suggested that co-targeting Aurka and Bcl-2 might be a potentially therapeutic strategy for DHL lymphoma.